2023
DOI: 10.1002/ajoc.202200720
|View full text |Cite
|
Sign up to set email alerts
|

Cobalt‐Catalyzed Diastereo‐ and Enantioselective Hydroarylation of Cyclopropenes with Arylboronic Acids

Abstract: Catalytic diastereo‐ and enantioselective hydroarylation of 3,3‐disubstituted cyclopropenes with easily accessible arylboronic acids promoted by a chiral phosphine‐Co complex is presented. Such a process represents an unprecedented Co‐catalyzed approach for direct introduction of a variety of aryl groups onto the cyclopropane motif, affording multisubstituted cyclopropanes in up to 86% yield with greater than 95 : 5 dr and 99 : 1 er.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 96 publications
0
1
0
Order By: Relevance
“…94 Recently, Meng et al have reported the arylation of 3,3-disubstituted cyclopropenes (Scheme 25b). 95 The introduction of various aryl groups onto the cyclopropane motif resulted in the formation of multi-substituted cyclopropanes with a yield of up to 86%. These cyclopropanes displayed a dr value greater than 95 : 5 and an ee value up to 98%.…”
Section: Regio-and Enantioselectivities Among Ligands Applied In Ahfmentioning
confidence: 99%
“…94 Recently, Meng et al have reported the arylation of 3,3-disubstituted cyclopropenes (Scheme 25b). 95 The introduction of various aryl groups onto the cyclopropane motif resulted in the formation of multi-substituted cyclopropanes with a yield of up to 86%. These cyclopropanes displayed a dr value greater than 95 : 5 and an ee value up to 98%.…”
Section: Regio-and Enantioselectivities Among Ligands Applied In Ahfmentioning
confidence: 99%